Effects of Relapse Forces on Periodontal Status of Mandibular Incisors Following Orthognathic Surgery - (:unkn) unknown (AMER ACAD PERIODONTOLOGY, 2008)
Background: In this case-control study, the relationship between the relapse forces and periodontal changes in the mandibular incisor region were investigated following orthognathic surgery. Methods: Mucogingival and alveolar changes in 36 subjects with mandibular prognathism were analyzed by clinical and roentgenographic methods just before mandibular setback surgery and 7.4 months postoperatively. The results were compared to two control groups: 36 subjects with no orthodontic history and 33 orthodontic patients. The mean age of the 105 subjects was 20.21 years. Results: The intergroup comparisons showed significant differences in all parameters, except for the plaque index and alveolar height measurements. By an incisor proclination of 3.3 mm and a tipping of +8.5 degrees (postoperative relapse: 0.8 mm and 0.14 degrees), the surgery group revealed significant changes in single parameters of both alveolar height and sulcus depth measurements. Conclusions: Compared to both control groups, the preoperative periodontal condition of the surgery patients was less acceptable than in the orthodontically treated patients, whereas subjects without braces presented the most ideal hygienic conditions. In the short term, the decompensation process prior to mandibular setback surgery did not affect periodontal structures significantly, and the current study did not find any negative effects of early postoperative relapse forces on the mandibular incisor area. J Periodontol 2008;79:2069-2077.
Keywords: Maxillofacial surgery; periapical tissue; prognathism; stability; tooth movement; ORTHODONTIC TREATMENT; TOOTH MOVEMENT; GINGIVAL RECESSION; ALVEOLAR BONE; MONKEYS; PROCLINATION; TISSUES; DISEASE; ROOT